Depletion of Toll-Like Receptor-9 Attenuates Renal Tubulointerstitial Fibrosis After Ischemia-Reperfusion Injury - Zheng, Haofeng; Zhang, Yannan; Li, Lei; Zhang, Rui; Luo, Zihuan; Yang, Zhe; Ye, Yongrong; He, Jiannan; Sun, Qiquan (Frontiers in Cell and Developmental Biology, 2021)
Toll-like receptor-9 (TLR-9) is a potent proinflammatory receptor that mediates renal injury. However, the reported effects of TLR-9 are contradictory. Here, using a traditional mouse AKI→CKD transition model, the roles of TLR-9 during the transition from acute kidney injury (AKI) to chronic kidney disease (CKD) were further explored. Using a TLR-9-/- mouse, the effects and mechanisms of TLR-9 were investigated. Loss of TLR-9 elicited no obvious effects as regards renal function or histology during AKI in the early phases (24 – 48 h), while TLR-9 KO attenuated renal fibrosis (as shown using fibronectin and collagen Ⅲ) and EMT (E-cadherin and α-SMA) on the long-term after AKI through the inhibition of macrophages infiltration, especially M2 macrophages. The roles of TLR-9 on macrophages were also explored using Raw264.7 macrophage cell line, and results indicated that the inhibition of TLR-9 on Raw 264.7 macrophages decreased the induction of M2 type macrophage in a dose-dependent manner. The roles of TLR-9 on renal tubular epithelial (RTE) cells were also explored. Conversely, TLR-9 depletion did not contribute to the improvement of fibrosis and EMT in vitro. Therefore, TLR-9 plays a critical role in the AKI→CKD transition. Attenuation of CKD post-AKI in the TLR-9 KO group mainly relies on the effects of TLR-9 on macrophages. These results also suggest that TLR-9 could be a therapeutic target for CKD.